Separate journeys : short stories by Indian women writers - Geeta Dharmarajan; Geeta Dharmarajan (London : Mantra, 1993)
Translated from various Indic languages.
Keywords: Short stories, Indic -- Translations into English; Indic fiction -- Women authors -- Translations into English